EFEKTIVITAS KOMUNIKASI PROGRAM #GenZHeTikYuk! DALAM MENGAMPANYEKAN HEMAT PLASTIK BAGI GENERASI Z DI PEKANBARU - Michiko Jamilah Frizdew; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The communication was stated to be effective if the stimulus delivered by the communicator can be developed and understood well by the receiver. According to Cutlip, etc. (2011), to see the effectiveness of communication in public relations programs, it needs the main principles. These are credibility, context, content, clarity, continuity and consistency, channel, and capability of the audience. One of the institution that implements public relations program, like campaigning issue to the public, is Department of Environment and Sanitation of Pekanbaru City. In order to help Department of Environment and Sanitation of Pekanbaru City to campaign their program to society, especially youth, they held Environmental Ambassador election. One of the campaign that was initiated by Pekanbaru’s Environmental Ambassador is #GenZHeTikYuk! (Generasi Z, Hemat Plastik Yuk!-Generation Z, Lets do plastic-free!). #GenZHeTikYuk! is a platisc-free campaign (bottle, glass, sachet, bag, etc), and focussing to reach generation Z (born in 1995-2012). This research existed to discover the effectiveness of communication of the #GenZHeTikYuk! program campaigning for a plastic-free generation Z in Pekanbaru. This research utilized a quantitative approach with descriptive types. The data in this research is found by questionnaires and library research. This research has reached a total of 10.304 peoples (the number of students from 12 schools who have been visited prior to the #GenZHeTikYuk!, the campaign, in October-November 2018). Then, with the Slovin formula, we receive 385 samples. The withdrawal samples technique in this research is proportionate stratified random sampling. The data was analyzed by a descriptive statistic. Based on this research, we get a mean of 3,5 for the seven indicators of the effectiveness of the communication that can be used. This shows that communication in the #GenZHeTikYuk! campaign is very effective in the campaign for a plastic-free generation Z in Pekanbaru. The criteria is based on scale distance of effectiveness judgment that be explained in research methodology chapter. Non-effective criteria is from 1,00-1,75 scale distance. Less effective criteria is from 1,76-2,50 scale distance. Effective criteria is from 2,51-3,25 scale distance. While, very effective criteria is from 3,26-4,00 scale distance. Key Words: Effetiveness Communication, Campaign, Environment Communication, Plastic Free